ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KUALITAS CORPORATE GOVERNANCE : STUDI EMPIRIS PADA PERUSAHAAN TERDAFTAR DI CORPORATE GOVERNANCE PERCEPTION INDEX TAHUN 2012-2015 - Ifvandaru Ramadhan; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This Study ain do examine the effect of firm’s characteristic that are divided into firm’s size, leverage, profitaility, growth of sales, Investment opportunity and ownership concentration on quality of corporate governance. Quality corporate governance proxied with scores of Corporate Governance Perception Index. In this research, the population of this research is all firms which are listed in Corporate Governance Perception Index (CGPI) by the Institute for Corporate Governance (IICG) in year 2012-2015. A total of 36 samples were used in this study with sample selection using the purposive sampling method. Analysis of the data used in this research is descriptive statistics, classical assumption test and hypothesis testing with multiple regression tested using SPSS softwareThe empirical results show that that the variable firm size, and ownership concentration have positively significant influenced, while leverage have negatively significant influenced on quality of Corporate Governance. Meanwhile, profitability, growth of sales , and investment opportunities has no significant influenced on on quality of Corporate Governance.